2022
DOI: 10.3390/foods11111562
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characteristics, and Advantages of Plant Protein-Based Bioactive Molecule Delivery Systems

Abstract: As a renewable resource, the market trend of plant protein has increased significantly in recent years. Compared with animal protein, plant protein production has strong sustainability factors and a lower environmental impact. Many bioactive substances have poor stability, and poor absorption effects limit their application in food. Plant protein-based carriers could improve the water solubility, stability, and bioavailability of bioactive substances by different types of delivery systems. In this review, we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 103 publications
(75 reference statements)
0
11
0
1
Order By: Relevance
“…Different packaging materials have different effects on the physical and chemical properties of the carrier. Some studies have found that protein and chitosan are more popular as materials for carrier preparation, and extensive studies have reported their favorable effects on increasing intestinal absorption and the bioavailability of plant polyphenols [ 14 ]. The encapsulation mechanisms of polyphenols by nanocarriers are diverse, including ionic gel, eutectic, condensation, encapsulation, emulsification, freeze-drying, and yeast encapsulation.…”
Section: Common Bio-based Polymer Nano-delivery Of Polyphenolic Compo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Different packaging materials have different effects on the physical and chemical properties of the carrier. Some studies have found that protein and chitosan are more popular as materials for carrier preparation, and extensive studies have reported their favorable effects on increasing intestinal absorption and the bioavailability of plant polyphenols [ 14 ]. The encapsulation mechanisms of polyphenols by nanocarriers are diverse, including ionic gel, eutectic, condensation, encapsulation, emulsification, freeze-drying, and yeast encapsulation.…”
Section: Common Bio-based Polymer Nano-delivery Of Polyphenolic Compo...mentioning
confidence: 99%
“…Protein is a multifunctional bio-based polymer with rich nutritional value and various functional properties, including emulsification, amphiphilicity, gelation, and foaming properties. Its unique chemical structure and functionality allow it to be engineered into nanoparticles, nanogels, nanoemulsions, nanofilms, and nanofibers that can deliver both hydrophilic and hydrophobic polyphenolic compounds [ 14 ]. The unique structure and physiological activity of polysaccharides, as bio-based polymers with a wide range of origins, allow them to be used as raw materials for the preparation of various types of nanocarriers and for the delivery of polyphenolic compounds [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Proteins represent excellent carriers of polyphenols due to their functional properties of emulsification, amphiphilicity, gelation, and foam formation. They can form nanoemulsions, nanogels, nanoparticles, nanofibers, and nanofilms, producing hydrophilic and hydrophobic polyphenolic compounds [ 136 ]. Likewise, polysaccharides, due to their structure and physiological activity, represent very suitable nanocarriers for encapsulating and administering polyphenols.…”
Section: Encapsulation Of Bioactive Compoundsmentioning
confidence: 99%
“…However, the bioaccessibility of protein is greatly challenged by harsh barriers in the upper gastrointestinal tract (GIT) (i.e., extreme gastric pH, intestinal protease, ionic strength, and long transit time). Colloidal delivery systems show great potential to encapsulate and protect protein cargoes during oral transmission [ 7 , 8 ]. These applications include hormones, enzymes, and probiotics [ 9 ].…”
Section: Introductionmentioning
confidence: 99%